Laminar shear stress promotes endothelial cell migration and inhibits cell apoptosis in the presence of hydroxyurea - Zeng, Y.; Liu, X. H.; Shen, Y.; Lai, Y.; Liu, X. J. (Cellular and Molecular Biology, 2011)
Cell migration plays important roles in both physiological and pathological processes. Recent studies have shown that hydroxyurea, which is an anti-proliferative inhibitor, can affect cell morphology and specific gene expression of endothelial cells (ECs). In vivo, the functions of ECs are modulated by shear stress. It is well known that shear stress can have effects on EC migration by affecting cell morphology, cytoskeletal arrangement and cell-cell junction, and activating mechanosensors, inducing the changes of signaling pathways, and then increasing or decreasing the expression of gene and protein. However, the influences of hydroxyurea on EC function under shear stress are still unclear. In present study, we investigated the effects of hydroxyurea on EC proliferation, apoptosis and migration under laminar shear stress. The results showed that hydroxyurea prevented growth of ECs in a dose-dependent manner. Hydroxyurea at 2 mM completely inhibited the proliferation of ECs. The results also demonstrated that hydroxyurea induced EC apoptosis, but it was inhibited by 15.27 dyn/cm2 laminar shear stress. Furthermore, shear stress induced cell migration in the presence of hydroxyurea. Therefore, 2 mM hydroxyurea, which completely inhibited the proliferation of HUVECs, could be used to eliminate any confounding effect of shear stress on proliferation in shear stress-induced cell migration. These results also do confirm that shear stress plays important roles in achieving and maintaining the stabilization of ECs.